ANSYS-based algorithms for a simulation of pultrusion processes. Issue 5 (4th April 2017) - Barkanov, Evgeny; Akishin, Pavel; Miazza, Nora L.; Galvez, Santiago
ABSTRACT: Pultrusion is a continuous and cost-effective process for a production of composite structural components with a constant cross-sectional area. To provide better understanding of the pultrusion processes, to support the pultrusion tooling design and process control, as well as to increase a reliability of the simulation results, two alternative finite element modeling approaches using the same continuous model with lumped material properties for the cured composite are developed, compared, and discussed. Each of them is constructed using the general-purpose finite element software ANSYS that results in considerable savings in development time and costs, and also makes available various modeling features of the finite element package. The first procedure is developed in ANSYS Mechanical environment and is based on the mixed time integration scheme and nodal control volumes method to decouple the coupled energy and species equations. The second procedure is performed using ANSYS CFX software with the cure reaction introduced as an additional variable. To demonstrate advantages and disadvantages of the developed procedures as well as to show their accuracy and reliability for the thermo-chemical simulation of pultrusion processes, two- and three-dimensional problems have been successfully analyzed.